2016
DOI: 10.1186/s40634-016-0064-2
|View full text |Cite
|
Sign up to set email alerts
|

Knee joint kinematics with dynamic augmentation of primary anterior cruciate ligament repair - a biomechanical study

Abstract: BackgroundDynamic augmentation of anterior cruciate ligament tears seems to reduce anteroposterior knee translation close to the pre-injury level. The aim of the present study is to biomechanically investigate the course of translation during a simulated early post-operative phase. It is hypothesized that anteroposterior translation is maintained at the immediate post-operative level over a simulated rehabilitation period of 50’000 gait cycles.MethodsEight fresh-frozen human cadaveric knee joints from donors w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 38 publications
0
13
0
Order By: Relevance
“…Their results confirm ACL protection during its biological recovery. The resistance to load is 60-80N, cycle 50,000, is similar in an intact joint and after the internal bracing [1,8].…”
Section: Introductionmentioning
confidence: 80%
“…Their results confirm ACL protection during its biological recovery. The resistance to load is 60-80N, cycle 50,000, is similar in an intact joint and after the internal bracing [1,8].…”
Section: Introductionmentioning
confidence: 80%
“…The polyethylene braid as well as the specimens are, however, subjected to plastic deformation and wear under cyclic loading. It can be assumed that spring shortening will, therefore, decrease with time [8].…”
Section: Discussionmentioning
confidence: 99%
“…Häberli et al performed a biomechanical study to evaluate the course of translation during a simulated early postoperative phase after dynamic augmentation of anterior cruciate ligament tears [ 45 ]. The authors found a low increase in anteroposterior translation of the knees that were investigated and noted that this procedure supported ACL repair during biological healing.…”
Section: Main Textmentioning
confidence: 99%
“…Furthermore, Häberli et al in a biomechanical study of eight fresh-frozen human cadaveric knee joints showed that anteroposterior translation of knees treated with this dynamic augmentation procedure is low [ 45 ]. In another cadaveric study, it was shown that DIS with a preload of 80 N restores knee joint kinematics to a level comparable to that of an ACL-intact knee and is therefore capable of providing knee joint stability during ACL healing [ 35 ].…”
Section: Main Textmentioning
confidence: 99%